2014
DOI: 10.1021/es5004439
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Impacts of Multiple Environmental Stress Factors on Estuarine Copepod Populations

Abstract: Many studies have focused on natural stress factors that shape the spatial and temporal distribution of calanoid copepods, but bioassays have shown that copepods are also sensitive to a broad range of contaminants. Although both anthropogenic and natural stress factors are obviously at play in natural copepod communities, most studies consider only one or the other. In the present investigation, we modeled the combined impact of both anthropogenic and natural stress factors on copepod populations. The model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Among the different IBMs developed for copepod so far, some effectively integrate and quantify the impact of both natural and anthropogenic forcing (Belleza et al, 2014;Kulkarni et al, 2014;Korsman et al, 2014) and showed the difference between individual-level and population-level sensitivities (Kulkarni et al, 2014). Those results confirm that models are valuable tools in predicting population-level responses from individual-level data and therefore ecological risk assessment of chemicals.…”
Section: Use Of Modeling As Tools To Integrate Effects From Individuamentioning
confidence: 77%
“…Among the different IBMs developed for copepod so far, some effectively integrate and quantify the impact of both natural and anthropogenic forcing (Belleza et al, 2014;Kulkarni et al, 2014;Korsman et al, 2014) and showed the difference between individual-level and population-level sensitivities (Kulkarni et al, 2014). Those results confirm that models are valuable tools in predicting population-level responses from individual-level data and therefore ecological risk assessment of chemicals.…”
Section: Use Of Modeling As Tools To Integrate Effects From Individuamentioning
confidence: 77%
“…When taking into account toxic exposure scenarios, and additional climate change-related stressors (e.g. salinity, pH, hypoxia and ultraviolet radiation), the simultaneous use of multiple stress functions is indispensable for informative model predictions [34, 77]. Multivariate stress equations may be established to yield more precise model predictions on interactive stress effects [19].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these models, toxic and nontoxic stressors were demonstrated to affect, e.g. copepods and eagles exposed to sediments in Dutch and Flemish deltas (Korsman et al, 2012; 2014).…”
Section: Ecological Variabilitymentioning
confidence: 99%